Hubungan Paritas, Jarak Beranak, dan Jenis Kelamin Terhadap Bobot Lahir Anak Sapi Limousin di Balai Pembibitan Ternak Unggul Hijauan Pakan Ternak Padang Mengatas - Ramadana, Alfitria; Ali Akbar, Syahro; Surtina, Dara (Jurnal Peternakan Mahaputra, 2023)
This study aims to determine the relationship between parity, calving distance, gender, and birth weight of Limousin calves at BPTU-HPT Padang Mengatas. The material for this research is recording data from 29 Limousin cattle consisting of parities I, II, and III which are kept at BPTU-HPT Padang Atasas. The method used in this research is the case study method and sampling was carried out using purpose sampling. Data was obtained by looking at the recording records for Limousin cattle at BPTU-HPT Padang Mengatas. The variables observed were parity, birth spacing, and gender as variable variables and birth weight as a fixed variable. Data analysis used multiple linear regression and processing using the SPSS 22 for Windows program to look for variables that were strongly related to birth weight. The results showed that the average birth weights at parity I, II, and III were 32.34 kg, 42.17 kg, and 44.14 kg. The increase in birth weight occurred starting from parity II and III amounting to 12.22% and 12.79%. The average calving distance between Calving Interval I and Calving Interval II was 588.79 days (19.62 months) and 550.41 days (18.35 months). The percentage of female calves at parity I and II was 51.72% while the percentage of male calves was 48.28%. At parity III the percentage of male calves was 37.93% while female calves were 62.07%. Based on the correlation results, an r-value of 59.2% shows that the variables tested have a strong relationship. This means that there is a correlation between parity, birth spacing, gender, and birth weight. X1 + X2 + X3